A coin hoard from Ayasuluk and the arrival of silver gigliati from Mediterranean Europe in early fourteenth-century western Anatolia - Baker, J; Pancar, L (Cambridge University Press, 2021)
In 1972 a hoard of eight fine silver coins was discovered in or near the baptistery of the basilica of St. John in Ayasuluk. It is now conserved at the Ephesus Archaeological Museum in Selçuk. The coins were minted in southern France, southern Italy, and on the island of Rhodes, between ca. 1303 and 1319 or perhaps a little later. Accordingly, a concealment date of ca. 1320 or a bit later is proposed. While the currency which they represent (the gigliato) is well known from other finds of the area, the present hoard is relatively early and from a particularly significant location. This currency found great success in commercial contexts in the eastern Aegean and western Anatolia during the period ca. 1325 – ca. 1370. By contrast, this study reveals two initial phases in the establishment and further dissemination of the gigliato in a concentrated part of western Anatolia, one in 1304 and another before and after ca. 1317. On both occasions the Catalans were instrumental in shaping these processes: initially as conquerors on behalf of the Byzantine emperors; and then, from their new base in Greece, as allies of the Aydınoğulları rulers of Ayasuluk. Additionally, it is proposed that this new gigliato currency might have been minted at Rhodes from the summer of 1319, after which it rapidly reached the Ephesus area in a military context.